Conceivability, Possibility, and A Posteriori Necessity: on Chalmers’s Argument for Dualism (Diametros, 2013)
Chalmers claims that the conceivability of zombies implies their possibility and he supports this claim by arguing that there is no gap between conceivability and possibility since no such gap can be generated by necessary a posteriori truths. I will argue that while Chalmers is right to the extent that there is no gap between conceivability and possibility within the standard Kripkean model of a posteriori necessity, his general conclusion is not justified. This is because there might be a posteriori necessity understood in some non-Kripkean way and Chalmers has not shown that no such alternative understanding of a posteriori necessity is available.